Understanding sovereign rating movements in euro area countries - Jan Brůha; Moritz Karber; Beatrice Pierluigi; Ralph Setzer (European Central Bank (ECB), 2017)
This paper investigates the link between sovereign ratings and macroeconomic fundamentals for a group of euro area countries which recorded rating downgrades amid the euro area sovereign debt crisis. We apply an elaborated econometric estimation technique, based on a Bayesian ordered probit model, to understand how the decisions of rating agencies can be explained by economic developments. The estimated model re-produces historical ratings by using a small number of economic and institutional variables, which seem to effectively summarize the large number of criteria used by Moody's, Standard & Poor's and Fitch in their assignment of sovereign ratings. Our results suggest that the size of the downgrades observed since the start of the sovereign crisis has been broadly in line with the deterioration of economic fundamentals for most countries.
Keywords: C25; G24; H63; H68; 330; euro area crisis; panel probit model; sovereign debt; sovereign rating